The imposible to witness - Mejía Toro, Jorge Mario (Estudios de Filosofía, 2003)
The writing The imposible to witness offers an interpretetion of Paul Celan’s nocturne Du Liegst by a reader who is not assumed as a addressee of the poem. In consecuence, the first moment of the reading follows the advice of the poem himself about keeping away the pretension of believing that a word’s sense lies in the meaning that we know. The second moment looks for the coordinates of sense in the punctuation of the poem, and its stratification in rime, to penetrate into the unknown of speech through unknown music. The third moment talks about the poem’s present and about its second person as sings of a poetry that does not offer nor have any hopes.